Why does performance management not perform?. Issue 4 (9th April 2018) - Cunha, Miguel Pina e; Vieira, Daniel Veiga; Rego, Arménio; Clegg, Stewart
Abstract : Purpose: The purpose of this paper is to ask why poor performance management practices persist in Portugal, in the middle of claims to increase productivity. Design/methodology/approach: An inductive micro-practice analysis is used to understand barriers to management practice that do not require massive institutional changes. Findings: The practice of performance management in Portugal typically displays three weaknesses: (1) insufficient planning (2) process and integrity issues, and (3) a non-meritocratic logic. Research limitations/implications: The paper discusses the important topic of persistence of bad practices, showing how institutionalized patterns might be difficult to eradicate even they are suboptimal. Practical implications: The authors identity key issues in the functioning of performance management, therefore helping managers in developing remedies to improve the quality of their practice. Originality/value: The paper explains the persistence of bad management practice whose continuity hinders not only organizations' effectiveness but also that of their members.